Application of Natural Science in Everyday Life: From Theory to Positive Impacts on Quality of Life - Suandayani, Ni Komang Tri (PT. Hafasy Dwi Nawasena, 2025)
Science education plays a crucial role in equipping learners with the skills needed to navigate 21st-century challenges. However, in Indonesia, science learning often remains limited to theoretical knowledge, with insufficient emphasis on process skills, higher-order thinking, and real-life applications. This study aimed to evaluate the effectiveness of an integrated instructional model combining Differentiated Challenge-Based Learning (DCBLM) and Problem-Based Creative Learning (PBCL) in improving students’ scientific competencies and perceptions of quality of life. Employing a mixed-methods design, 120 participants including secondary and university students engaged in science activities for twelve weeks. Quantitative data were collected through validated Science Process Skills (SPS) and Higher-Order Thinking Skills (HOTS) tests, along with a Quality of Life (QoL) perception survey, while qualitative insights were gathered through semi-structured interviews. Results from paired-sample t-tests showed significant improvements in SPS (M = 62.4 to 78.9), HOTS (M = 58.7 to 74.3), and QoL perceptions (M = 3.21 to 3.78), all with large effect sizes. Thematic analysis revealed learners’ ability to apply science in daily life, increased environmental awareness, and enhanced confidence in problem-solving. These findings confirm that the hybrid model not only strengthens scientific knowledge and thinking skills but also promotes sustainable practices and well-being. The study highlights the potential of contextualized science education to bridge pedagogical innovation with classroom realities and contribute to the Sustainable Development Goals (SDGs)..